(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study determined how commercial banks in Cross River State are engaging in ethical marketing practices and community involvement practices all aspects of corporate social responsibility practices. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. Survey research design was adopted for the study. Population for the study comprised 578 community representatives in Cross River State. A sample size of 216 was drawn using multi-stage sampling technique. For effective investigation a 24 item structured, validated questionnaire was used for collection of data from the respondents. The reliability of the instrument was established using split half method and a reliability co-efficient of 0.82 was obtained. Data collected were analyzed using mean scores for the research questions. The hypotheses were tested using One-way analysis of variance. The findings of the study revealed among others that the commercial banks in Cross River State poorly engage in corporate social responsibility practices. It was recommended among others that commercial bank owners should organize in-house ethical training to help their employees make appropriate ethical decisions to meet the ethical concerns of their consumers and the host community.